1990
DOI: 10.1159/000200402
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Survival and Binding of Plant Lectins during Small Intestinal Passage and Their Effectiveness as Growth Factors

Abstract: The effects on the small intestine and the growth of rats of six pure plant lectins: PHA (Phaseolus vulgaris); SBL (Glycine maxima); SNA-I and SNA-II (Sambucus nigra); GNA (Galanthus nivalis) and VFL (Viciafaba), covering most sugar specificities found in nature, were studied in vivo. Variable amounts, 25% (VFL) to 100% (PHA, GNA) of the lectins administered intragastrically, remained in immunochemically intact form in the small intestine after 1 h. All lectins, except GNA, showed binding to the brush border o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
127
0
2

Year Published

1995
1995
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(144 citation statements)
references
References 6 publications
15
127
0
2
Order By: Relevance
“…Other lectins have already been shown to rapidly cover cell and tissue surfaces. Epithelial cells from several insect guts were found to be covered by Galanthus nivalis (GNA) and Con-A lectins added to the insect diet [17,18]. The accumulation and persistence of lectins on cell and tissue may additionally act by disrupting the multiple metabolic processes carried out by this cell or this tissue [18].…”
Section: Discussionmentioning
confidence: 99%
“…Other lectins have already been shown to rapidly cover cell and tissue surfaces. Epithelial cells from several insect guts were found to be covered by Galanthus nivalis (GNA) and Con-A lectins added to the insect diet [17,18]. The accumulation and persistence of lectins on cell and tissue may additionally act by disrupting the multiple metabolic processes carried out by this cell or this tissue [18].…”
Section: Discussionmentioning
confidence: 99%
“…Ingested PHA, which is highly resistant to gut proteases, binds to the brush border cells of the intestine where it is rapidly endocytosed. When the lectin enters the cells, it induces an enhanced metabolic activity that eventually leads to hyperplasia and hypertrophy of the small intestine (Pusztai et al, 1990). Moreover, ingestion of PHA or raw beans causes acute nausea followed by vomiting and diarrhea.…”
Section: The Toxlclty Of Plant Lectins For Hicher Animalsmentioning
confidence: 99%
“…However, small intestinal weight and structure are not influenced by camostate (unlike raw soybean meal), which suggests disparate effects on small intestine and pancreas. Pusztai et al (1990) reported on the intestinal growth promoting effect of lectins in rats and suggested that lectins might play a role in the replacement of epithelial cells. Trypsin inhibitors can only partially account for the antinutritive effects as it was demonstrated by DiPietro and Liener (1989).…”
mentioning
confidence: 99%